Shadow pricing market access: a trade benefit function approach - Nancy H. Chau; Rolf Färe (University of Bonn, Center for Development Research (ZEF), 2008)
Appropriate assessment of the social value of market access is at the core of a broad range of inquiries in trade research. A selection include: the appraisal of industry-level production and consumption distortions due to selective trade liberalization and partial tax reform; the construction of national-level quantity indicators of market access consistent with welfare change, and the use of international trade re-balancing as sanctions to discourage trade agreement violations, or as compensation in trade dispute settlement. In order to obtain shadow prices, we propose a new approach integrating the Luenberger benefit function and the directional output distance function. This yields a trade benefit function which represents trade preferences à la Meade in the context of a canonical general equilibrium model of trade. We first show that our approach is in keeping with well-established and commonly used measurement techniques of trade welfare, for the standard trade expenditure function is in fact dual to the trade benefit function. We then show that this dual relation allows for a direct retrieval of the shadow values of net imports from the trade benefit function. The usefulness and operationality of our approach is then demonstrated in a series of applications and simulations. – – Kern eines breiten Spektrums von Untersuchungen der Handelsforschung ist eine angemessene Bewertung des sozialen Wertes des Marktzugangs. Dabei werden z.B. untersucht: Auswirkungen von Liberalisierungen des Handels und partiellen Steuerreformen auf die Produktion von Industriegütern und auf das Konsumverhalten; Konstruktion nationaler Qualitätsindikatoren für den Zugang zu Märkten und damit verbundenen Wohlfahrtsniveaus, und die internationalen Handelsumlenkungen als Sanktionen, um die Verletzung getroffener Handelsvereinbarungen einzudämmen, oder als Kompensation in Handelsdisputen. Um Schattenpreise zu erhalten, schlagen wir einen neuen Ansatz vor, in welchem die ,,Luenberger benefit function“ und die ,,directional output distance function“ berücksichtigt werden. Daraus ergibt sich die ,,trade benefit function“, welche Handelspräferenzen à la Meade im Kontext eines kanonischen Gleichgewichtsmodells des Handels darstellt. Zunächst zeigen wir, dass unser Ansatz mit bereits etablierten und gängigen Messtechniken der Wohlfahrtseffekte des Außenhandels im Einklang steht, denn die ,,standard trade expenditure function“ ist komplementär zur ,,trade benefit function“. Anschließen zeigen wir, dass diese Komplementarität eine direkte Ableitung der Schattenwerte der Netto-Importe aus der ,,trade benefit function“ zulässt. Anhand von Fallbeispielen und Simulationen stellen wir schließlich noch den Nutzen und die Anwendbarkeit unseres Ansatzes dar.
Keywords: 330